Pengaruh Profitabilitas, Growth Opportunity, Likuiditas Terhadap Struktur Modal Pada Masa Pandemic COVID-19 (Studi Kasus Pada Perusahaan Industri Textil Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020) - Zeinal Abidin; Budi Wahono; Nurhidayah Nurhidayah (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abtract This research was conducted with the aim of analyzing the effect of Profitability (ROE), Growth Opportunity and Liquidity (CR) on Capital Structure during the Covid-19 pandemic. The population used in this study were tekstil and garment industry companies listed on the Indonesia Stock Exchange (IDX) in the 2020 period. The sample used in this study was a purposive sampling technique. Companies included in the criteria for this study consisted of 11 companies during the study period of 1 year. The data collection method used in this research is the documentation of the financial statements of tekstil and garment industry companies which are listed on the IDX. The analysis used is multiple linear regression by testing the hypothesis using the f test and t test. The results showed that the simultaneous test on the Profitability (ROE), Growth Opportunity, and Liquidity (CR) variables had a simultaneous effect on the capital structure (DER). Whereas in the t test the Profitability (ROE) and liquidity (CR) variables had a significant effect on the capital structure (DER), while the Growth Opportunity variable had no significant effect on the Capital Structure (DER). Keywords : Profitabilitas, Growth Opportunity, and Likuiditas